Background: Malaysian Audiology Scientific Conference (MASCO) 2025 - Ismail, Afzarini Hasnita; Rahmat, Sarah; Lee, Onn Wah; Mohd Sakeri, Nurul Syarida; Wan Mohamad, Wan Najibah (Thieme, 2025)
This editorial summarizes the 7th Malaysian Audiology Scientific Conference (MASCO) 2025, held in Penang, Malaysia, under the theme “Building Strong Foundations: The Evolution of Evidence-Based Practice in Audiology.” The conference gathered 111 audiologists and 26 students, featuring six plenary sessions by international and local experts on translational practice, auditory processing disorder, tinnitus management, and pediatric hearing loss. Participants presented 14 oral papers, 15 three-minute pitches, and 23 e-posters showcasing innovative diagnostic tools and clinical applications. MASCO 2025 emphasized bridging research and practice through interdisciplinary collaboration and localized strategies to advance audiology service delivery in Malaysia.